2019
DOI: 10.1210/js.2019-00196
|View full text |Cite
|
Sign up to set email alerts
|

Practice Variation in the Care of Subclinical Hypothyroidism During Pregnancy: A National Survey of Physicians in the United States

Abstract: Evidence regarding the effects of subclinical hypothyroidism (SCH) on adverse pregnancy outcomes and the ability of levothyroxine (LT4) treatment to prevent them is unclear. Available recommendations for the management of SCH during pregnancy are inconsistent. We conducted a nationwide survey among physicians assessing their knowledge of and current practices in the care of SCH in pregnancy and compared these with the most recent American Thyroid Association (ATA) recommendations. In this cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
2
5
0
3
Order By: Relevance
“…In addition, this equipoise is reflected by the heterogeneity of practice patterns observed across geographic regions in our study. This is consistent with a US utilization study that showed variations in prescribing patterns across different specialists, 13 as well as studies examining clinical perceptions of practices for SCH management in pregnancy 31,32 . This heterogeneity may be explained by emerging concerns 33 about the harms of overtreating, and uncertainties about the benefits of treating SCH with levothyroxine during pregnancy 34‐36 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, this equipoise is reflected by the heterogeneity of practice patterns observed across geographic regions in our study. This is consistent with a US utilization study that showed variations in prescribing patterns across different specialists, 13 as well as studies examining clinical perceptions of practices for SCH management in pregnancy 31,32 . This heterogeneity may be explained by emerging concerns 33 about the harms of overtreating, and uncertainties about the benefits of treating SCH with levothyroxine during pregnancy 34‐36 .…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with a US utilization study that showed variations in prescribing patterns across different specialists, 13 as well as studies examining clinical perceptions of practices for SCH management in pregnancy. 31 , 32 This heterogeneity may be explained by emerging concerns 33 about the harms of overtreating, and uncertainties about the benefits of treating SCH with levothyroxine during pregnancy. 34 , 35 , 36 Future high‐quality studies are warranted to examine the safety and effectiveness of levothyroxine for women with SCH on health outcomes of mothers and their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de los estudios establecen que el valor objetivo en embarazadas debe ser menor a 0,5 mUI/L. Para pacientes de alto riesgo, se recomiendan dosis que logren la supresión de TSH, como se realiza fuera del embarazo (48) . Los casos de cáncer de tiroides resistente a yodo radiactivo pueden ser tratados con inhibidores de tirosina quinasa.…”
Section: Tratamientounclassified
“…Schilddrüsenerkrankungen sind bei Frauen präkonzeptionell, in der Schwangerschaft und der postpartalen Zeit häufig anzutreffen, wobei man akzeptieren muss, dass es noch immer wissenschaftliche Diskussionen um die jeweiligen Hormongrenzwerte in diesem Kontext gibt und das praktische Vorgehen in der klinischen Routine recht heterogen ist [36][37][38]. Diverse Beobachtungsstudien haben in der Vergangenheit einen Zusammenhang zwischen einer latenten Hypothyreose bzw.…”
Section: Schlussfolgerungenunclassified